IMMERSIVE INNOVATION FOR SOCIAL CHANGE: VIRTUAL AND AUGMENTED REALITY IN COMMUNITY-BASED ENTREPRENEURSHIP - Haruto Takahashi; Yui Nakamura; Ethan Tan; Rana Wijaya (Yayasan Adra Karima Hubbi, 2026)
Service learning has gained recognition as an effective pedagogical approach that bridges academic learning with community service. This study examines the integration of service learning in higher education, evaluating its impact on students’ academic performance, personal development, and community engagement. The research aimed to explore how service learning can enhance students’ practical skills, critical thinking abilities, and social responsibility, while also contributing to the community’s well-being. A mixed-methods approach was employed, combining quantitative surveys to assess students’ academic performance and qualitative interviews to understand their personal experiences with service learning. The results indicate that students who participated in service learning programs showed significant improvements in their ability to apply theoretical knowledge in real-world contexts, with 75% of students reporting an increase in problem-solving and teamwork skills. Additionally, service learning fostered a greater sense of civic responsibility, with students expressing a stronger commitment to community service and social justice. The study concludes that integrating service learning into higher education curricula promotes holistic student development and contributes to community-based solutions. The findings suggest that service learning should be further incorporated into educational frameworks to provide students with meaningful opportunities for engagement and personal growth.